Propagation dynamics of the solid–liquid interface in Ge upon ns and fs laser irradiation. (8th September 2022) - Casquero, Noemi; Ruiz de Galarreta, Carlota; Fuentes-Edfuf, Yasser; Solis, Javier; Wright, C David; Siegel, Jan
Abstract: Monitoring the laser-induced melting and solidification dynamics of Ge upon laser irradiation is an enormous challenge due to the short penetration depth of its liquid phase. In this work, real-time pump-probe experiments in combination with finite element calculations have been employed to investigate the melting and solidification dynamics of germanium upon ns and fs laser pulse irradiation ( λ = 800 nm). Excellent agreement between experiments and simulations allowed us to indirectly determine additional time- and depth-dependent information about the transformation dynamics of germanium, including the thickness evolution of the molten layer, as well as its melting and solidification velocities for the two pulse durations for different fluences. Our results reveal considerable differences in the maximum thickness of the molten Ge superficial layers at sub-ablative fluences for ns and fs pulses, respectively. Maximum melt-in velocities of 39 m s −1 were obtained for ns pulses at high fluences, compared to non-thermal melting of a thin layer within 300 fs for fs pulses already at moderate fluences. Maximum solidification velocities were found to be 16 m s −1 for ns pulses, and up to 55 m s −1 for fs pulses. Weak signs of amorphization were observed for fs excitation, suggesting that the lower limit of solidification velocities for a complete amorphization is above 55 m s −1 . In addition, we show high precision measurements of the melt-in velocities over the first 20 nm by means of fs microscopy with sub-ps temporal resolution. Here, differences of the melt-in process of several orders of magnitude were observed, ranging from virtually instantaneous melting within less than 2 ps even for a moderate peak fluence up to 200 ps for fluences close to the melting threshold.